2022
DOI: 10.1002/ctm2.1026
|View full text |Cite
|
Sign up to set email alerts
|

Promising use of immune cell‐derived exosomes in the treatment of SARS‐CoV‐2 infections

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection is persistently threatening the lives of thousands of individuals globally. It triggers pulmonary oedema, driving to dyspnoea and lung failure. Viral infectivity of coronavirus disease 2019 (COVID‐19) is a genuine challenge due to the mutagenic genome and mysterious immune‐pathophysiology. Early reports highlighted that extracellular vesicles (exosomes, Exos) work to enhance COVID‐19 progression by mediating viral transmission, replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…At present, there are a lot of researches and reviews on Exos and extracellular vesicles against COVID‐19, while most of them focus on the role and possibility of treatment in specific sources, 2,5–7 without the whole research progress in the era of COVID‐19 outbreak 8 . A recent review published in Clinical and Translational Medicine presents important insights into current immunopathology and the applications of immune cell‐derived Exos for the immunotherapy of COVID‐19 9 . Exos derived from immune cells could trigger novel anti‐SARS‐CoV‐2 immune responses, which are effective in reducing the inflammatory response.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…At present, there are a lot of researches and reviews on Exos and extracellular vesicles against COVID‐19, while most of them focus on the role and possibility of treatment in specific sources, 2,5–7 without the whole research progress in the era of COVID‐19 outbreak 8 . A recent review published in Clinical and Translational Medicine presents important insights into current immunopathology and the applications of immune cell‐derived Exos for the immunotherapy of COVID‐19 9 . Exos derived from immune cells could trigger novel anti‐SARS‐CoV‐2 immune responses, which are effective in reducing the inflammatory response.…”
Section: Figurementioning
confidence: 99%
“…Compared to antibody therapy and small molecule, the ability to home at its origin tissue, cell processes control through mediating multifunction and simple differentiation and labeling give Exos numerous advantages in the treatment of COVID‐19 9 . While there is no definite theoretical basis for the immune modulation mechanisms driven by Exos, especially corresponding dynamic structure alterations involved in the interactions among Exos, virions, and host cells.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Intercellular communication is an essential hallmark of multicellular organisms and can be mediated through direct cell-cell contact or the transfer of secreted molecules (9). Increasing studies have shown that immune cells participate in cellular communication by secreting exosomes (10,11). Among the immune cell-derived exosomes, T cell-derived exosomes have recently been reported to be involved in antitumor effects in cancer immunotherapy by mimicking the role of parental cells (12)(13)(14)(15).…”
mentioning
confidence: 99%